Microbiological assay for ceftazidime injection - De Haro Moreno, Andréia [UNESP]; Salgado, Herida Regina Nunes [UNESP] (Oxford University Press (OUP), 2007)
A simple, sensitive, and specific biodiffusion assay for the antibacterial ceftazidime was developed using a strain of Staphylococcus epidermidis (ATCC 12228) as the test organism. Ceftazidime was measured in powder for injection at concentrations ranging from 100 to 400 μg/mL. The calibration graph for ceftazidime was linear (r2 = 1), and the method validation showed that it was precise (relative standard deviation = 0.415) and accurate. The results obtained by biodiffusion assay were statistically calculated by linear parallel model and by means of regression analysis and were verified using analysis of variance. It was concluded that the microbiological assay is satisfactory for in vitro quantification of the antibacterial activity of ceftazidime in pharmaceuticals.